2015
DOI: 10.4238/2015.september.22.18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of single nucleotide polymorphisms of the signal transducer and activator of transcription 3 gene (STAT3) associated with body measurement and carcass quality traits in beef cattle

Abstract: ABSTRACT. Previous studies have shown that the signal transducer and activator of transcription 3 gene (STAT3) is involved in lipid storage and energy metabolism, suggesting that STAT3 is a potential candidate gene that affects body measurement and carcass quality traits in animals. Therefore, the aim of this study was to identify polymorphisms in bovine STAT3 and to analyze their possible associations with body measurement and carcass quality traits in 493 individuals of 2 native Chinese cattle breeds: Qinchu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Interestingly, a recent mouse study showed that STAT3 regulates differentiation of brown adipose tissues (BAT), involved primarily in burning energy [ 17 ]. Genetic variants of STAT3 in cattle directly influence body size and carcass quality traits [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent mouse study showed that STAT3 regulates differentiation of brown adipose tissues (BAT), involved primarily in burning energy [ 17 ]. Genetic variants of STAT3 in cattle directly influence body size and carcass quality traits [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we also observed that the upregulation of STAT3 expression regulated the cell cycle and apoptosis via the JAK/STAT signaling pathway ( Figure S5 ). STAT3 stimulates fat deposition in cattle [ 48 ]. Therefore, the milk replacer used in the present study might have increased fat deposition in the liver, thereby negatively affecting the hepatic function.…”
Section: Discussionmentioning
confidence: 99%